Multi-Track Diplomacy Fiqh of Nahdlatul Ulama in Countering Islamophobia in Netherlands - Muhammad Taufiq; Muhammad Noor Harisudin; Maimun Maimun (Universitas Islam Negeri Jakarta, 2022)
Islamophobia is a global issue, leading to discrimination, violence, and hatred against Muslims in the Netherlands. In response to this, the Special Branch of Nahdlatul Ulama of the Netherlands (PCINU of the Netherlands) is among the Indonesian diaspora campaigning for the moderation of “Islam Nusantara” through multi-track diplomacy fiqh, a holistic approach emphasizing interdependence in politics, economics, and socio-culture. This paper discusses the multi-track diplomacy fiqh of PCINU of the Netherlands in fighting against Islamophobia in the country. As a non-governmental socio-religious organization, PCINU of Netherlands play a role and strategy in assisting the diplomacy of the Ministry of Foreign Affairs of the Republic of Indonesia in spreading the “Islam Nusantara” idea to counter Islamophobia. This article is based on empirical research with fiqh al-siyāsah and maqāṣid al-sharī’ah analysis. This study finds that, in countering Islamophobia, PCINU of the Netherlands uses a multi-track diplomacy strategy that successfully spreads friendly, anti-terror, tolerant and moderate Islam. Even though PCINU has not fully employed all Multi-track fields, it has successfully encountered islamophobia and promoted peaceful Islam through Islam Nusantara.Keywords: multi-track Diplomacy Fiqh; Moderation; Islamophobia; Islam Nusantara; world peace AbstrakIslamofobia menjadi isu global yang menimbulkan diskriminasi, kekerasan, dan kebencian terhadap Muslim, termasuk di Belanda. Dalam merespons hal ini, Pengurus Cabang Istimewa Nahdlatul Ulama Belanda (PCINU Belanda) sebagai diaspora Indonesia mengampanyekan moderasi Islam Nusantara melalui fikih diplomasi multitrack. Tulisan ini mendalami strategi fikih diplomasi PCINU Belanda dalam memerangi Islamofobia di Belanda. Sebagai organisasi sosial keagamaan non pemerintah, PCINU Belanda memiliki peran dan strategi dalam membantu diplomasi Kementerian Luar Negeri Republik Indonesia dalam menebarkan moderasi “Islam Nusantara” merespons Islamofobia. Studi ini adalah penelitian empiris dengan pendekatan fikih siyasah dan maqāṣid al-sharī’ah. Dalam merespons Islamofobia, PCINU Belanda menggunakan strategi diplomasi multitrack yang berhasil menebarkan Islam yang ramah, anti teror, toleran, dan moderat. Meskipun PCINU belum sepenuhnya menggunakan semua bidang multitrack, namun berhasil menghadapi islamofobia dan mempromosikan Islam yang damai melalui Islam Nusantara.Kata Kunci: multi-track diplomacy; moderasi; islamfobia; Islam Nusantara; perdamaian dunia